2011
DOI: 10.1371/journal.pone.0025213
|View full text |Cite
|
Sign up to set email alerts
|

PI3K and ERK-Induced Rac1 Activation Mediates Hypoxia-Induced HIF-1α Expression in MCF-7 Breast Cancer Cells

Abstract: BackgroundHypoxia-inducible factor 1 (HIF-1α) expression induced by hypoxia plays a critical role in promoting tumor angiogenesis and metastasis. However, the molecular mechanisms underlying the induction of HIF-1α in tumor cells remain unknown.Methodology/Principal FindingsIn this study, we reported that hypoxia could induce HIF-1α and VEGF expression accompanied by Rac1 activation in MCF-7 breast cancer cells. Blockade of Rac1 activation with ectopic expression of an inactive mutant form of Rac1 (T17N) or Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 57 publications
6
78
0
Order By: Relevance
“…S3A). Activation of the MAPK/ERK and Akt/mTOR pathways has been reported to enhance HIF-1α protein synthesis [6, 7]. We also observed that IMQ treatment promoted the phosphorylation of ERK1/2 and Akt in BCC and SCC12 cells, indicating that the MAPK/ERK and Akt/mTOR signaling pathways were activated (Fig.…”
Section: Resultssupporting
confidence: 72%
“…S3A). Activation of the MAPK/ERK and Akt/mTOR pathways has been reported to enhance HIF-1α protein synthesis [6, 7]. We also observed that IMQ treatment promoted the phosphorylation of ERK1/2 and Akt in BCC and SCC12 cells, indicating that the MAPK/ERK and Akt/mTOR signaling pathways were activated (Fig.…”
Section: Resultssupporting
confidence: 72%
“…Hu et al (18) demonstrated that EGF stimulates migration of hepatoma cell line HepG2 through GEP100-dependent activation of the Arf6/ERK/Rac1 signaling pathway. Du et al (16) reported that the PI3K and ERK-induced Rac1 activation is required for hypoxia-induced HIF-1α expression in breast cancer cells. Jones et al (15) proposed that the association of PLC-γ1 with complexes containing GIT1 and β-Pix is essential for its role in integrin-mediated cell spreading and motility, during which the activation of Cdc42 and Rac1, which are downstream of PLC-γ1, is crucial since depletion of Cdc42 or Rac1 abolishes the elongated cell phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of Rac1 at Ser71 has been reported to modulate downstream signaling by inhibiting the interaction of Rac1 with its effectors (12). In addition, phosphatidylinositol-4,5-bisphosphate 3-kinase/protein kinase B (PI3K/Akt), mitogen-activated protein kinase kinase/extracellular signal-regulated kinase (MEK/ERK) and phospholipase C γ1 (PLCγ1) -mediated signal transduction have been implicated in the Rac1 signaling pathway in various human cancer cell lines (15)(16)(17)(18). Therefore, the current study also aimed to establish the effects of inhibiting these pathways on Rac1 activation, and the ability of PKG II to directly phosphorylate Rac1.…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, NF-B and HIF-1␣ are shown to be the downstream targets of PI3K/Akt and/or ERK (22)(23)(24). Thus, to investigate the role of these signaling nodes in gemcitabine-induced activation of NF-B and HIF-1␣, we treated the PC cells with specific pharmacological inhibitors of Akt (LY294002) and ERK (PD98059) prior to stimulation with gemcitabine.…”
Section: Activation Of Nf-b and Hif-1␣ Involves Ros-mediated Activatimentioning
confidence: 99%